Faith seeking understanding - Vorster, J.M (Reformed Theology in Africa Series, 2022)
The debate between faith and science is an ongoing and dynamic conversation marked by the need to consistently factor in new data generated by the sciences, and new perspectives developed in theology. In this book, a group of theologians and ethicists provide insights into the debate from a faith perspective. The basic thesis permeating the discussions is that faith and science are capable of enriching and complementing each other, albeit in their own unique way. What unifies faith and science is the search for truth. What differentiates them is the unique lenses they employ to find the truth. In the end, both scientists and theologians must take into account all the pathways and lenses that lead us to a better understanding of reality. This study presents concrete examples of how theological knowledge and scientific data can be fruitfully used and integrated to develop new horizons of understanding. The general aim of this contribution was to narrow in on some of the burning themes that are driving the faith or science scholarly debate. Each contributor highlights a different aspect of the debate. The topics addressed include theoretical perspectives on the science-faith relation, the ancient scientific worldview of the creation narratives in Genesis, evolution and human origins, science and African Pentecostalism, faith and the Fourth Industrial Revolution, science and transhumanism, science and traditional medicine, and the role that faith and science can play in the human quest for meaning. Most of the contributors approach the topic from a post-foundationalist and postpositivist epistemological point of view. A wide range of hermeneutical methods is employed, ranging from systematic biblical-theological perspectives to literary and source criticism. Analytical, normative and existential philosophical arguments are also utilised throughout the course of the book. The most important contribution of the book lies in the transdisciplinary perspectives that emanate from the discussion. The ways in which the authors go about integrating theological and scientific perspectives to address ultimate questions about meaning and to inform moral discourse show that religion still has an important role to play in a world increasingly shaped by technological rationality. At the same time, it indicates that religion and science do not have to stand in conflict with each other. If the two lenses on reality engage in mature dialogue, they can enrich, inform and, on some occasions, even correct each other. The target audience of this book includes theological scholars, natural scientists and science philosophers. This book contains no plagiarism, and none of the work has been published elsewhere.